Vaccine expert Peter Hotez on the COVID-19 pandemic—and how a new vaccine can help end it - Hotez, Peter J. (2022)
Peter Hotez spoke at an ILRI townhall meeting on 11 March 2022 about the about the current state of the pandemic as well as the progress of his newly developed COVID-19 vaccine. Interview by Eric Fèvre, joint appointee at ILRI and Professor of Veterinary Infectious Diseases at the Institute of Infection and Global Health, University of Liverpool.